Tembang Dolanan Jawa sebagai Media Pendidikan Karakter - Annisa Mawaddah Mutiara Sari; Sofia Hartati; Tjipto Sumadi (Indonesian Journal of Educational Counseling, 2020)
JAVANESE TEMBANG MUSIC AS A CHARACTER EDUCATION MEDIA. The purpose of this study was to study about Dolanan Song can be character media or develop character in Sidogemah Village. Dolanan song is a tradition in Sidogemah Village to develop the character of young children. This research was carried out for 6 months, housed in Sidogemah Village, Sayung Subdistrict, Demak Regency Data collection techniques using the method of observation, documentation, and interview. This research used etnography method with descriptive qualitative. Then the results are obtained that Dolanan song is a song from generation to generation in the land of Java, containing deep meaning. Parenthood is conveyed by parents to children as a form of character education. The process of character education by parents of children in Sidogemah Village, Sayung Subdistrict, Demak Regency is developed before going to sleep, at school, and when children play. The process of character building of children through dolanan song in Sidogemah Village, Sayung District, Demak Regency can be classified into three, namely knowing, doing and caring.